The immunomodulatory effect of lithium as a mechanism of action in bipolar disorder - Szałach, Łukasz P.; Lisowska, Katarzyna A.; Cubała, Wiesław J.; Barbuti, Margherita; Perugi, Giulio (Frontiers in Neuroscience, 2023)
Bipolar disorder (BD) is a chronic mental disorder characterized by recurrent episodes of mania and depression alternating with periods of euthymia. Although environmental and genetic factors have been described, their pathogenesis is not fully understood. Much evidence suggests a role for inflammatory mediators and immune dysregulation in the development of BD. The first-line treatment in BD are mood-stabilizing agents, one of which is lithium (Li) salts. The Li mechanism of action is not fully understood, but it has been proposed that its robust immunomodulatory properties might be one of the mechanisms responsible for its effectiveness. In this article, the authors present the current knowledge about immune system changes accompanying BD, as well as the immunomodulatory effect of lithium. The results of studies describing connections between immune system changes and lithium effectiveness are often incoherent. Further research is needed to understand the connection between immune system modulation and the therapeutic action of lithium in BD.